1990
DOI: 10.1159/000288386
|View full text |Cite
|
Sign up to set email alerts
|

A Psychological Support Concept and Quality of Life Research in a Liver Transplantation Program: An Interdisciplinary Multicenter Study

Abstract: Considering the increasing number of liver transplantations with longer periods of transplant function, there is a growing need for quality of life research in the field. In addition to lethality, mortality and rehabilitation, parameters of ‘quality of life’ are to be evaluated: the patient’s rating of his subjective physical symptoms, psychological condition (anxiety, depression and mental adjustment), social reintegration and life satisfaction. This paper describes our psychological support program that has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Gender may also be important; in this study, 73% of subjects were male. Kober et al 20 found that the QOL reported by men was less than the one reported by women, whereas in a later study Moore et al did not find any difference. 21 Results of QOL studies that used different tools should be compared with caution, however.…”
Section: Discussionmentioning
confidence: 86%
“…Gender may also be important; in this study, 73% of subjects were male. Kober et al 20 found that the QOL reported by men was less than the one reported by women, whereas in a later study Moore et al did not find any difference. 21 Results of QOL studies that used different tools should be compared with caution, however.…”
Section: Discussionmentioning
confidence: 86%
“…Other studies using questionnaire data reported patients rating their QoL as good to excellent after OLT, 9,36,37 and Lowe et al 38 stated such ratings are not significantly different from community norms. Interestingly, Kober et al 15 found QoL reported by men was less than that reported by women. Post hoc examination of the present data showed no gender differences on recipients' ratings of their QoL (t 22 ϭ 1.19; P Ͻ .05).…”
Section: Discussionmentioning
confidence: 96%
“…13 An article from the Helsinki group provided the first major attempt to compare patients pre-OLT and post-OLT on neurological state. 14 Even so, their study and a similar design from Kober et al 15 were limited in the scope of domains assessed and contained method problems. Our own group extended this pre-post design by the addition of control groups and reported significant improvements in recipients' mood and work status after OLT.…”
mentioning
confidence: 99%
“…Of the 5505 studies, 58 met our inclusion criteria (39 from MEDLINE, 11 from Embase, and 8 from manual searches). 4, We combined multiple reports of the same patient populations: the Chicago-Hamburg group, 49 …”
Section: Identified Studiesmentioning
confidence: 99%